Solidaritas Kekristenan Sebagai Wujud Dari Altruisme Terhadap Orang Miskin (Suatu Tinjauan Etis) - Brisco Nathanael Sihombing (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
This paper examines the act of Christian solidarity as a form of altruism towards the poor which will be discussed qualitatively descriptively, namely by conducting a literature study in which there is an understanding of theological ethics. Altruism, as opposed to egoism, is an act that arises from oneself to assist others on a larger scale than oneself. It cannot be ruled out that altruism can be used as a moral basis to form solidarity with the poor. Solidarity means that we share what other people feel, precisely the sense of solidarity with the poor. Poor, in this case, is not only material, but poor people also feel poor in spirit. This research emphasizes that it is essential to cultivate a sense of Christian solidarity towards the poor, which is a manifestation of altruism with a Christian foundation that is so strong in its foundation with the law of love. Therefore, Christians participate in altruistic actions based on the law of love for the poor, both materially and spiritually poor. Making altruism an indication of morality will be a good first step to increasing a solid sense of concern among people to reduce poverty.